Perceptions of New Roles for Libraries and Librarians in Big Data Adoption - Ganessingh, Ray (My University, 2024)
The emergence of Big Data creates an opportunity for traditional libraries to transform into massive data libraries. When large amounts of data are produced and harvested, massive stores of valuable information are also created. This data can then be tracked through the use of a combination of data tagging and metadata to catalogue the sets in their different formats. Data analysis methods suited to advanced technologies are therefore invaluable for analyzing the extensive and diversified collections of linked data that will constitute the shared research resources in libraries of the future. The results of these methods can be used to improve library collection planning, visualization of data and provide quality search results. Consequently, they will also influence myriad areas of libraries’ frameworks, including human and literature resources, service modernization, technological adoptions, and the construction of structures. With the growing momentum of the introduction of Big Data into libraries, the roles of librarians will also evolve. In addition to creating policies for data privacy and security, and training communities in data literacy and the values of research, they will also assume responsibility for managing research data to make it accessible and reusable by others, and for making decisions on how to expand open-source content, and how to select and purchase resources, including AI tools to facilitate large data processing and storage. Among these ideas, the poster presentation will also identify areas for new research and an education paradigm to improve library operations.
Poster presented at 53rd Association of Caribbean University Research and Institutional Libraries (ACURIL) Conference held on 12–16 May, 2024 in Georgetown, Guyana.
Keywords: Big data; Librarians